Authentication system for e-certificate by using RSA’s digital signature - Kritsanapong Somsuk; Mongkhon Thakong (Universitas Ahmad Dahlan, 2020)
Online learning and teaching become the popular channel for all participants, because they can access the courses everywhere with the high-speed internet. E-certificate is being prepared for everyone who has participated or passed the requirements of the courses. Because of many benefits frome-certificate, it may become the demand for intruders to counterfeit the certificate. In this paper, Rivest-Shamir-Adleman (RSA)’s digital signature is chosen to signe-certificate in order to avoid being counterfeited by intruders. There are two applications to managee-certificate. The first application is the signing application to sign the sub image including only participant’s name in e-certificate. In general, the file of digital signature is divided frome-certificate. That means, both of them must be selected to compare each other in checking application. In fact, the solution will be approved when each pixel of participant’s name is equal to each part from the decrypted message at the same position. In experimental session, 40 e-certificatesare chosen for the implementation. The results reveal that the accuracy is 100% and both of signing and checking processes are completed rapidly fast, especially when signing application is applied with Chinese remainder theorem (CRT) or the special technique of CRT. Therefore, the proposed method is one of the best solutions to protect e-certificate from the forgery by intruders.